Designing a Web-Based Internship Information System for Vocational High Schools - Hardison Hardison; Riki Mukhaiyar; Mukhlidi Muskhir; Waskito Waskito; Afdal Luthfi (Postgraduate, University of Mataram, 2025)
This research aims to develop a web-based information system to overcome administrative inefficiencies in managing the Field Work Practice (PKL) program at Vocational High Schools (SMK). Using the prototype development method, the research followed three stages: collecting user requirements, developing and refining a mock-up, and evaluating system performance through Black Box Testing, specifically assessing system functionality, user interface, and user experience. The results show a reduction in time for administrative tasks such as student enrollment, schedule management, and industry collaboration. The system also achieved improved data accuracy through features such as real-time progress tracking and automated notifications. End-user feedback indicated high satisfaction with the system's usability and interface design. In addition, the system also supports government initiatives for technology integration in education by encouraging collaboration between schools, students and industry partners. The study concludes that the web-based system effectively improves administrative efficiency, promotes transparency and accountability, and prepares students to become a technology-based workforce